Ecological influences on the difference in δ15N and δ13C values between fish tissues: implications for studies of temporal diet variation. Issue 4 (15th April 2013) - Michaud, Wendy K.; Dempson, J. Brian; Reist, James D.; Power, Michael
Abstract: Temporal diet changes can be detected by comparing δ 13 C and δ 15 N values between tissues with different isotopic turnover times. However, other factors contribute to disparities in δ 13 C and δ 15 N signatures between tissues and could confound the interpretation of stable isotope data. We examined the effects of ecological factors on differences in muscle and liver δ 13 C and δ 15 N signatures of Arctic charr [ Salvelinus alpinus, (L.) ] to determine whether their effects were large enough to influence studies of diet change. In addition, we examined whether differences in lipid content accounted for a significant portion of the differences in δ 13 C values between tissues. Results indicated that life history, diet, reproductive status and gender had significant effects on the differences in δ 13 C values between tissues, while gender and diet significantly affected differences in δ 15 N values. Differences in % lipid content between tissues also explained approximately 74% of the observed variation in the difference in δ 13 C values between tissues. The differences in δ 13 C values observed between muscle and liver tissues may be partially explained by physiological differences in lipid storage and use between tissues associated with ecological factor effects. These results demonstrate that ecological factors other than a change in diet can influence the differences in δ 13 C and δ 15 N signatures between muscle and liver tissues. However, the impact of ecological factors on studies of diet change depends on how the magnitude of the factor effects compared with a biologically meaningful change in diet.